Mental Health Effects as a Consequence of Early Sports Specialization in College Athletes: A Multicenter Study - Jared J. Lutsic; Seth E. Lutsic; David S. Ibrahim; Jason D. Robinson; Kevin M. Tong; Toufic R. Jildeh; Mathew R. Saffarian; Nathan J. Fitton (Clinical Journal of Sport Medicine, 2026)
Objective: This study examines the impact of early sport specialization on mental health in NCAA athletes. Specialized athletes report higher stress, weight changes, fatigue, decreased sport enjoyment, and greater burnout. Few studies have explored this link, and none have focused on NCAA athletes who specialized before college. This is the first multicenter study to assess these mental health domains related to specialization. Design: Retrospective cohort study. Setting: Sport, Action, Finding, Evaluation Consortium. Participants: In total, 257 collegiate athletes from the NCAA's 3 levels of competition: Divisions I, II, and III. Intervention: N/A. Main Outcome Measures: Athletes completed a questionnaire about their demographics, specialization status, burnout-related perceptions, academic outcomes, weight loss, and sleep. Results were analyzed based on specialization status, which was classified using a published 3-point scale. Results: Highly specialized athletes reported less enjoyment ( P = 0.033), reduced athletic accomplishment ( P = 0.01), poorer academic performance ( P = 0.043), more weight loss ( P = 0.043), and worse sleep ( P < 0.001) than low-specialized athletes. Moderately specialized athletes had a reduced sense of athletic accomplishment ( P = 0.002) and more daytime sleepiness ( P = 0.002) than low-specialized athletes. Female athletes reported more unintentional weight loss ( P < 0.01) and less sport enjoyment ( P = 0.036) than male athletes. Pressure to specialize before college was linked to worse outcomes in all domains except weight loss ( P = 0.871). Conclusions: Higher specialization correlates with negative mental health outcomes, including reduced sport enjoyment and accomplishment, sleep, and more weight loss. Pressure to focus on 1 sport before college is a stronger predictor of adverse outcomes than specialization itself.